Equilateral triangular slot antenna for communication system and GNSS RO sensor of GAIA-I microsatellite - Awaludin A.; Tetuko Sri Sumantyo J.; Ito K.; Gao S.; Munir A.; Zafri Baharuddin M.; Edi Santosa C. (Institute of Electronics, Information and Communication, Engineers, IEICE, 2023)
3D printers; Antenna feeders; Antenna reflectors; Bandwidth; Circular polarization; Directive antennas; DNA sequences; Global positioning system; Radio navigation; Reflection; Satellite antennas; Satellites; Axial ratio bandwidth; Global Navigation Satellite Systems; GNSS; Micro satellite; Reflector; Simulated performance; Triangular slot antennas; Wideband antenna; Slot antennas